UNIQUENESS IN AMONI ARABANI'S POETRY (World Bulletin of Social Sciences, 2023)
This article analyzes some poems of Amoni Arabani, a poet of Fergana Valley during the period of national renaissance, a disciple of Furkat. The topics raised in some of the poet’s lyrical works on social themes are studied by classifying them into poetic categories